Different Approaches to Detect “Nanobacteria” in Patients with Kidney Stones: an Infectious Cause or a Subset of Life? - Ansari, Hani; Akhavan Sepahi, Abbas; Akhavan Sepahi, Mohsen (Urology Journal, 2017)
Purpose: This research focused on the detection of nanobacteria in kidney stones of 30 Iranian patients without adding fetal bovine serum (FBS) to the culture media. Materials and Methods: Nanobacteria were isolated from a nephro-ureterolithiasis extract of the urinary tract and kidney of patients and were cultured in the laboratory. The growth of nanobacteria was monitored using a spectrophotometer, and with inverted microscopy technique, their crystallization was analyzed after two days. The images from atomic force microscopy (AFM), transmission electron microscopy (TEM) and scanning electron microscopy (SEM) indicated the morphology and demonstrated the size of the cultured nanobacteria which is between 60 and 160 nm. Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) were used to study the chemical composition, surface functional groups and crystal structure of the igloo-like nanobacteria shell. FTIR spectra in the region of 1000 to 1200 cm-1 and the XRD peaks provided evidence that the main components of the nanobacteria shell were apatite-based compounds. Results: Nanobacteria infected all the 27 patients with apatite kidney stone, and none of the three patients who had uric acid kidney stone were infected as confirmed by the cultivation of the stones samples. The results showed that nanobacteria might play a fundamental role in the formation of apatite-based kidney stones. Conclusion: The biomineralization ability of nanobacteria may lead to calcification of the soft tissues, which in turn may result in other diseases. It is also suggested that nanobacteria may be a factor in calcification-related diseases and disorders with poorly characterized etiologies. This research with its different approaches, clarified significant doubts that nanobacteria act as contaminant, warranting continued investigation of its role in other diseases.